The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s44201-022-00003-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department-based cancer screening interventions

Abstract: Background Emergency department patients are disproportionately non-adherent with the United States Preventive Services Task Force cancer screening recommendations, making the emergency department a target-rich environment for interventions aimed at increasing the uptake of cancer screening. Promotion of cancer screening in the emergency department has the potential to address health disparities and to reach patients that experience significant barriers to accessing preventive care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 79 publications
0
14
1
Order By: Relevance
“…Increasing evidence has demonstrated that the ED is in a unique position to address disparities in cancer prevention and screening. 7 As demonstrated in this work, ED patients are disproportionally non-adherent with the USPSTF cancer screening recommendations and, thus, the ED is a desirable location to reach these populations that otherwise would not have access to preventive services. 20 Examples of success in addressing cancer prevention/screening in the ED include a randomized controlled trial by Adler et al 21 Their study demonstrated the feasibility and efficacy of a behavioral intervention to increase uptake of cervical cancer screening among ED patients at an urban, academic ED.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Increasing evidence has demonstrated that the ED is in a unique position to address disparities in cancer prevention and screening. 7 As demonstrated in this work, ED patients are disproportionally non-adherent with the USPSTF cancer screening recommendations and, thus, the ED is a desirable location to reach these populations that otherwise would not have access to preventive services. 20 Examples of success in addressing cancer prevention/screening in the ED include a randomized controlled trial by Adler et al 21 Their study demonstrated the feasibility and efficacy of a behavioral intervention to increase uptake of cervical cancer screening among ED patients at an urban, academic ED.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that ED patients are disproportionately non-adherent with the USPSTF cancer screening recommendations. 7 Disparities in cancer screening, including socioeconomic status (SES) and racial/ethnic status are pervasive in the literature, and has been further exacerbated by the coronavirus 2019 pandemic. 8 Despite the fact that EDs serve as a safety net for vulnerable populations who suffer from health disparities, limited work has explored the missed opportunities for cancer screening among ED patients.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
See 1 more Smart Citation
“…Little to no literature exists examining the association with eventual cancer diagnosis in association with an ED visit, offering opportunities for addressing cancer prevention and cancer screening in the context of an ED visit. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the ED sees a high volume of patients who are not up-to-date with USPSTF cancer screening recommendations. For example, previous cross-sectional [ 12 ] and experimental work [ 13 ] using research associates to interview patients has demonstrated that a substantial proportion of women in the ED are not adherent with cervical and/or breast cancer guidelines (for a thorough review of ED-based cancer screening research, see Adler, Abar, and Chiao [ 14 ]). To date, however, limited work has been dedicated to developing scalable and sustainable methods for identifying ED patients in need of colorectal cancer screening.…”
Section: Introductionmentioning
confidence: 99%